Membangun Karakter Kepemimpinan dan Kemandirian Santriwati dalam Rangka Peningkatan Kualitas Akademik di Pondok Putri Ridwan Anwarul Halimy - Sa'di, Kholisus; Rila Hardiansyah; Muhammad Arief Rizka; Ahmad Yani (Fakultas Ilmu Pendidikan dan Psikologi, 2025)
The purpose of this research is that Pondok Putri Ridwan Anwarul Halimy can become a model for women's Islamic boarding schools that successfully integrate character development with sustainable academic quality improvement, so as to be able to produce a generation of intelligent, independent, and visionary Muslim women. The method of implementing this service activity uses a participatory and collaborative approach consisting of four main stages: preparation, training implementation, program implementation, and continuous mentoring. The leadership and independence character development program carried out at Pondok Putri Ridwan Anwarul Halimy showed positive results. Through structured training, students can develop their leadership and independence skills, which in turn improves their academic quality and strengthens their moral character. Approaches based on Islamic values and Islamic boarding schools as well as the application of collaborative methods such as peer teaching and collaborative projects have proven effective in forming students who are more independent, responsible, and ready to face life's challenges. This program can be used as a model for strengthening the character of students in other Islamic boarding schools, with a more structured and sustainable approach.